Dynamics of cellular immunity in critical conditions in patients with traumatic brain injury - Ashurov T.Kh; Toshev I.I (Genius Journals, 2023)
This article will focus on changes in cellular immunity in patients with multiple severe traumatic brain injury. Changes in the functional activity of neutrophils and lymphocytes, including subpopulations of CD3+, CD4+ and CD8+, can be observed in seriously ill patients with injuries and in the intensive care unit. Most severe traumatic brain injuries are complicated by infectious diseases, and secondary infections are the cause of these complications
Keywords: CD3; CD4; CD8; subpopulation